2015
DOI: 10.1002/eji.201444635
|View full text |Cite|
|
Sign up to set email alerts
|

Th17‐related cytokines contribute to recall‐like expansion/effector function of HMBPP‐specific Vγ2Vδ2 T cells after Mycobacterium tuberculosis infection or vaccination

Abstract: Whether cytokines can influence the adaptive immune response by antigen-specific γδ T cells during infections or vaccinations remains unknown. We previously demonstrated that, during BCG/Mycobacterium tuberculosis (Mtb) infections, Th17-related cytokines markedly upregulated when phosphoantigen-specific VγVδ2 T cells expanded. In this study, we examined the involvement of Th17-related cytokines in the recall-like responses of Vγ2Vδ2 T cells following Mtb infection or vaccination against TB. Treatment with IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…The single-cell suspension (4 ml) was obtained by gently grounding spleen through a 75 µm cell strainer and underlayed by 4 ml pre-warmed Lymphocyte-M (Cedar Lane Lab, Burlington, VT, USA). Density-gradient centrifugation was performed at 1,250 x g for 25 min to isolate splenocytes (16,17). Cells were counted and diluted to a final concentration of 5x10 6 cells/ml in RPMI-1640 medium (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 10 U/ml penicillin, 10 µg/ml streptomycin and 10% fetal bovine serum (Invitrogen; Thermo Fisher Scientific, Inc.).…”
Section: Animalsmentioning
confidence: 99%
“…The single-cell suspension (4 ml) was obtained by gently grounding spleen through a 75 µm cell strainer and underlayed by 4 ml pre-warmed Lymphocyte-M (Cedar Lane Lab, Burlington, VT, USA). Density-gradient centrifugation was performed at 1,250 x g for 25 min to isolate splenocytes (16,17). Cells were counted and diluted to a final concentration of 5x10 6 cells/ml in RPMI-1640 medium (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 10 U/ml penicillin, 10 µg/ml streptomycin and 10% fetal bovine serum (Invitrogen; Thermo Fisher Scientific, Inc.).…”
Section: Animalsmentioning
confidence: 99%
“…This in vivo correlate prompts a hypothesis or possibility that Th17-related cytokines involve expansion or recall-like responses of Vγ2Vδ2T cells after infections. Now new NHP studies showed that IL-17A/IL-17F, IL-22 or IL-23 could expand phosphoantigen HMBPP-stimulated Vγ2Vδ2 T cells from BCG-vaccinated macaques but hardly from naïve animals [23 •• ] (Figure 2). IL-23 induced greater expansion than other Th17-related cytokines [23 •• ].…”
Section: Broad Repertoires Of Cytokines Involve Expansion Recall-likmentioning
confidence: 99%
“…Now new NHP studies showed that IL-17A/IL-17F, IL-22 or IL-23 could expand phosphoantigen HMBPP-stimulated Vγ2Vδ2 T cells from BCG-vaccinated macaques but hardly from naïve animals [23 •• ] (Figure 2). IL-23 induced greater expansion than other Th17-related cytokines [23 •• ]. Consistently, Mtb infection of macaques also enhanced the ability to IL-17/IL-22 or IL-23 to expand HMBPP-stimulated Vγ2Vδ2 T cells (Figure 2).…”
Section: Broad Repertoires Of Cytokines Involve Expansion Recall-likmentioning
confidence: 99%
See 2 more Smart Citations